Sistem Informasi Pembayaran SPP Di Lembaga Kursus Matematika Dan Bahasa Inggris (Studi Kasus Di Kumon Ngringo Palur) - Iswanti, Ristia Marta; Hastomo, Mursid Dwi; Pantjarani, Ari (Politeknik Harapan Bangsa Surakarta, 2024)
KUMON is one of the educational institutions that implements tuition payments. Thepayment system carried out in the agency is still carried out by recording in the paymentlogbook and copying in the number processing software. This causes a less efficient processand there are often errors in the data input process because it is still done using books. Inaddition, the process of finding student payment data also has difficulties because it must bedone by opening the payment notebook one by one. Based on these problems, the authorformulates a problem, namely how to design and create a web-based SPP paymentinformation system. The author limits the problem to the design and creation of an SPPpayment information system according to the one running in the KUMON institution. Theinformation system that the author discusses is able to process class, student and paymentdata starting from the data input process and displaying payment reports and arrears.Information systems are designed web-based so that they can be accessed using computer orcommunication devices. The purpose of this study is to design and create an SPP paymentinformation system at the KUMON institution which is expected to help the paymentadministration department to process input and report data quickly and efficiently, besidesthat the data search process can be carried out quickly and accurately. The author uses theSDLC (System Development Life Cycle) method in the process of developing an informationsystem. The author uses PHP programming language and MySQL databases for theinformation system development process.Keywords: Information Systems, payment, PHP, MySQL